2022
DOI: 10.2147/copd.s349694
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Dysregulated Mechanisms and Candidate Gene Markers in Chronic Obstructive Pulmonary Disease

Abstract: Purpose This study aimed to identify candidate gene markers that may facilitate chronic obstructive pulmonary disease (COPD) diagnosis and treatment. Methods The GSE47460 and GSE151052 datasets were analyzed to identify differentially expressed mRNAs (DEmRs) between COPD patients and controls. DEmRs that were differentially expressed in the same direction in both datasets were analyzed for functional enrichment and for coexpression. Genes from the largest three modules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
(54 reference statements)
1
1
0
Order By: Relevance
“…42 It can also promote autism symptoms of WAGR by perturbing these mechanisms in the developing human brain. 43 A recent study also verified that PRRG4 was the main methylation marker of COPD, 44 which is verified by our study as well. The potential mechanism of ZNF678 in COPD remains unclear.…”
supporting
confidence: 88%
“…42 It can also promote autism symptoms of WAGR by perturbing these mechanisms in the developing human brain. 43 A recent study also verified that PRRG4 was the main methylation marker of COPD, 44 which is verified by our study as well. The potential mechanism of ZNF678 in COPD remains unclear.…”
supporting
confidence: 88%
“… 11 Lin et al have ever identified candidate genetic biomarkers in COPD process via in silico analysis. 12 Herein, we applied an integrated analysis of GEO dataset containing COPD and control subjects by multiple bioinformatics approaches to investigate the potential biomarkers and molecular mechanisms for COPD.…”
Section: Introductionmentioning
confidence: 99%